Why don’t students of baccalaureate get the b1 proficiency level when leaving high school - Espinoza Espinosa, Camila (2024)
The research investigates the notable differences in English proficiency among third year baccalaureate students from two public and two private schools in Ibarra. It emphasizes the disparity in language skills between public and private education. The focus is on identifying the factors that affect students’ ability to reach level B1 of the Common European Framework of Reference for Languages (CEFR). Despite English being a mandatory part of Ecuador’s education system, students’ proficiency levels, especially in public schools, remain significantly low. Employing a comprehensive mixed-methods approach, the research integrates both qualitative and quantitative methodologies. Surveys and interviews were conducted, engaging students, educators, and administrative staff from both public and private educational institutions across the Imbabura province. This contrast among public and private schools in Ibarra shows the factors influencing their ability to achieve B1 level in the CEFR. Despite mandatory English education in Ecuador, proficiency remains notably low, especially in public schools. Conclusions drawn from the research underscore the imperative of continual teacher development initiatives, targeted strategies to support student motivation, and fostering collaborative partnerships with higher education institutions and community organizations to fortify English language education. Recognizing the crucial role of parental involvement in cultivating a supportive learning environment, efforts to engage parents are emphasized with the support of the authorities of each institution.